Localization of filamin in smooth muscle (The Rockefeller University Press, 1986)
The distribution of contractile and cytoskeletal proteins in smooth muscle has been mapped by immunocytochemical methods, with special reference to the localization of the actin-binding protein, filamin. Immunolabeling of ultrathin sections of polyvinylalcohol-embedded smooth muscle distinguished two domains in the smooth muscle cell: (a) actomyosin domains, made up of continuous longitudinal arrays of actin and myosin filaments, and (b) longitudinal, fibrillar, intermediate filament domains, free of myosin but containing actin and alpha-actinin- rich dense bodies. Filamin was found to be localized specifically in the latter intermediate filament-actin domains, but was excluded from the core of the dense bodies. Filamin was also localized close to the cell border at the inner surface of the plasmalemma-associated plaques. In isolated cells the surface filamin label showed a rib-like distribution similar to that displayed by vinculin. It is speculated that the two domains distinguished in these studies may reflect the existence of two functionally distinct systems: an actomyosin system required for contraction and an intermediate filament-actin system, with associated gelation proteins, that is responsible, at least in part, for the slow relaxation and tone peculiar to smooth muscle.